Factors influencing self-efficacy for self-management among adult people with human immune deficiency virus on antiretroviral therapy in public hospitals of south-west Ethiopia - Abdisa, MisganaTesgera; Gindaba, Bekan Gudeta; Zerihun, Ebisa (Frontiers in Psychology, 2024)
Introduction Self-management is crucial for effective HIV management, and self-efficacy is a mechanism for achieving it, but there is limited evidence on variables that affect self-efficacy. This study aimed to identify factors influencing self-efficacy for self-management among adults on antiretroviral therapy in resource constraint settings. Methods A cross-sectional study was conducted among 422 adult people on antiretroviral therapy in southwest Ethiopia from March to April 2022. Face-to-face interviews were used to gather data using a structured questionnaire on the self-efficacy measure. The data were then imported into Epi Data version 4.2 and exported to SPSS version 26. Descriptive statistics, independent tests, one-way analysis of variance, Pearson correlation, and multivariate linear regression were used to analyze the data. The predictors with p-value of less than 0.05 were declared statistically significant. Results A total of 413 adults on antiretroviral therapy were interviewed with response rate of 97.9%. The total mean score of self-efficacy for self-management was 15.12 (±2.22) out of 24. Higher age, gender of the female, divorced, duration of diagnosis, and drug side effects were negatively predictors of low self-efficacy. Higher schooling, urban residence, better income, and the use of reminders positively influenced self-efficacy for self-management. Conclusion The study found low self-efficacy among adults on antiretroviral therapy and higher age, female gender, HIV duration, and presence of drug side effects were associated with lower self-efficacy, while higher schooling, better income, and use of reminder use were associated with higher self-efficacy for self-management. Further research is needed to determine the causal relationship between these variables and self-efficacy.